STRATEGI KOMUNIKASI PUBLIC RELATIONS PT.NUSA ALAM LESTARI DALAM MEMBANGUN CITRA POSITIF PADA MASYARAKAT ASAM JUJUHAN KABUPATEN DHARMASRAYA PROVINSI SUMATERA BARAT - Prayogi "; Genny Gustina Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Nusa Alam Lestari is a company in the field of natural resource utilizationengaged in exploration and marketing of coal. PT. Nusa Alam Lestari has a publicrelations or public relation department to assist management in running publicrelations and management functions. Mining and factory area of PT. Nusa Alam Lestariaddress the relationship between PT. Nusa Alam Lestari with the people of AsamJujuhan which can be said generally good, but there is still the possibility of occurrenceof problems that at any time can disrupt the company. PT. Nusa Alam Lestari commit tothe community as a communication strategy to improve the corporate image in the eyesof the jujuhan acid community. The purpose of this research is to know the model ofpublic relations communication strategy of PT. Nusa Alam Lestari in building a positiveimage in the Jujuhan Asam community of Dhamasraya Regency, West SumateraProvince. To Know the activity of public relations communication strategy of PT. NusaAlam Lestari in building a positive image on the people of Asam Jujuhan DhamasrayaRegency, West Sumatera Province which has been done for. To know what factors affectthe communication strategy Public Relations PT. Nusa Alam Lestari in building apositive image in the Jujuhan Asam community of Dhamasraya Regency, WestSumatera Province.In this study used qualitative research methods with the presentation ofdescriptive analysis. This research uses descriptive qualitative method, collecting datausing interview, documentation and literature study.Model of public relations communication strategy PT. Nusa Alam Lestari inbuilding a positive image on the people of Asam Jujuhan Dhamasraya Regency WestSumatra Province, Public Relations PT. Nusa Alam Lestari is structurally undergeneral manager with the nature of centralization or corporate funnel for employees,community and stakeholders. Communication strategy activities Public Relations PT.Nusa Alam Lestari in building a positive image in the community of Jujuhan AcidDhamasraya Regency West Sumatra Province which has been done by determining thecontents of the message is packed with the appropriate concept accepted by thecommunity. Factors affecting communication activities Public Relations PT. Nusa AlamLestari in building a positive image in the people of Asam Jujuhan. Divided intosupporting and inhibiting factors.